독거노인의 고독감과 죽음준비에서 자기통제감의 매개효과 - 윤은경(Eun-Gyeong Yun); 조윤득(Yeun-Duk Jo) (한국콘텐츠학회 논문지, 20(8), 2020)
The purpose of this research is to investigate the mediating effect of sense of self-control in the relationship between loneliness and preparation for death of seniors living alone. The research results can be summarized as follows: First, the difference between the feeling of loneliness and the feeling of self-control, depending on the personal trait of the subject was examined. The subjects that are male, have no faith, and have their own houses showed a more intense feeling of loneliness than subjects that are female, have faith, and have their own houses, respectively. Also, the subjects that have their own houses and are engaged in economic activities showed a more intense feeling of self-control. Second, when it comes to the relationship between loneliness and preparation for death, seniors who had been hospitalized and had lower loneliness showed higher levels of preparation for death. Third, the analysis on the effect on sense of self-control revealed that the younger and the lower the loneliness, the higher the sense of self-control. Fourth, such sense of self-control had a partial mediating effect in the relationship between loneliness and preparation for death. Therefore, this research suggested measures to promote activities to prepare for death by decreasing loneliness and strengthening sense of self-control of the elderly living alone. 본 연구는 독거노인의 고독감과 죽음준비 관계에서 자기통제감의 매개효과를 살펴보고자 한 것이다. 연구대상은 B 지역 소재 노인복지관과 재가복지기관의 서비스를 이용하고 있는 독거노인으로 설문지 총 201부를 분석하였다. 연구결과를 요약하면 다음과 같다. 첫째, 조사대상자 개인특성에 따른 고독감과 자기통제감의 차이를 살펴 본 결과, 남성이 여성보다, 종교가 없는 경우, 그리고 자가 소유가 아닌 경우 고독감이 높게 나타났으며, 월소득이 높고, 자가 소유이며 경제활동을 하고 있는 경우에 자기통제감이 높게 나타났다. 둘째, 고독감과 죽음준비와의 관계에서는 입원력이 있고 고독감이 낮은 경우에 죽음준비 활동이 높아지는 것으로 확인되었다. 셋째, 자기통제감에 대한 영향요인을 분석한 결과, 고독감이 낮을수록 자기통제감이 높은 것으로 나타났다. 넷째, 이러한 자기통제감은 고독감과 죽음준비와의 관계에서 부분매개효과를 가지는 것을 알 수 있었다. 따라서 향후 독거노인의 고독감을 낮추고 자기통제감을 강화하여 죽음준비를 활성화할 수 있는 방안을 제안하였다.